2003
DOI: 10.1007/s000180300001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of N -acetylcysteine actions

Abstract: Oxidative stress generated by an imbalance between reactive oxygen species (ROS) and antioxidants contributes to the pathogenesis of arthritis, cancer, cardiovascular, liver and respiratory diseases. Proinflammatory cytokines and growth factors stimulate ROS production as signaling mediators. Antioxidants such as N-acetylcysteine (NAC) have been used as tools for investigating the role of ROS in numerous biological and pathological processes. NAC inhibits activation of c-Jun N-terminal kinase, p38 MAP kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
903
1
33

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,210 publications
(966 citation statements)
references
References 160 publications
29
903
1
33
Order By: Relevance
“…The activation of the Erk-p38 MAPK pathway is likely attributable to the oxidative stress induced by BU, because Erk and p38 are sensitive to ROS [16,17,31,36]. It has been shown that the major route of BU metabolism is through GSH-S-transferase catalyzed conjugation to GSH [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of the Erk-p38 MAPK pathway is likely attributable to the oxidative stress induced by BU, because Erk and p38 are sensitive to ROS [16,17,31,36]. It has been shown that the major route of BU metabolism is through GSH-S-transferase catalyzed conjugation to GSH [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…NAC is a potent antioxidant that can inhibit oxidative stress by directly scavenging ROS and replenishing GSH [31]. If ROS production mediates BU-induced senescence via activation of the Erk-p38 MAPK pathway, we would expect that NAC should have the ability to inhibit BUinduced senescence while suppressing the activity of the Erk-p38 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC may increase intracellular cysteine and subsequent GSH levels (Deneke, 2000). The molecular mechanism of NAC was recently reviewed (Zafarullah et al, 2003). NAC affects transcription factors, apoptosis and cell survival, all of which are important targets in treating neurodegenerative diseases.…”
Section: Thiol-based Antioxidantsmentioning
confidence: 99%
“…It has been suggested that caution should be applied when NAC is used as an antioxidant since it also possesses reducing capability via its thiol-disulfide exchange activity independent of its antioxidative or free radical scavenging properties [40,41]. NAC has been shown to prevent apoptosis induced by methyl-2-cyano-3,12-dioxooleana-1,9-dien-28-oate [42].…”
Section: Discussionmentioning
confidence: 99%